Depiction of Harihararka or Hariharapitamaharka - Temples of India Project Team (Jio Institute, 2024)
This is the east-facing elevation of the central shrine in the Neelkanth Mahadev Temple. The bhadra (central projection) image on the exterior wall facing east, contains a unique composite image called the Harihararka (or Hariharapitamaharka), which is a depiction wherein Shiva, Vishnu, and Surya (and plausibly Brahma) have been incorporated into one sculpture. The three-faced figure is shown sitting on a chariot of seven horses, holding the attributes of all its representative deities.